Identification of Permeable Structures and Heat Source in the Geothermal Working Area of Galunggung Volcano and the Heat Source Connectivity to the Karaha-Cakrabuana Area Using Gravity Data - Leo Agung Prabowo; Salahuddin Husein; Sismanto Sismanto (Geological Engineering Department Universitas Gadjah Mada, 2023)
Galunggung volcano area is a geothermal concession area that adjacent with Karaha-Cakrabuana concession area with a distance around 1 km. Indonesian Government planning to build power plant in 2025 so additional research needed to support the plan. Gravity survey could help in identifying permeable structure (fault) as well as heat source to a certain depth. The results of data processing showed the presence of faults seen on the FHD, SVD, and ABL residual maps, while for heat sources it was shown from the closed contour patterns on the ABL, residual, and regional maps. Derivative analysis in strengthens the position and type of fault from the match between the maximum FHD value and zero SVD value. From these results, identified the existence of three faults in the study area and were all identified as normal faults. 3D modelling gave a picture of density contrast in research area. From the section profile that pass through Galunggung and Telaga Bodas crater, heat source was interpreted as density with value 2.8 – 3.0 gr/cm3 and marked by orange to red color that coincide below Galunggung crater and continoued to Talaga Bodas crater at depths below -3000 masl. This indicate that both concession area was connected.